The Contribution of Parenting Styles to the Academic Achievement of Elementary School Students: Kontribusi Pola Asuh Orang Tua terhadap Prestasi Belajar Siswa Sekolah Dasar - Wahyu Trianto, Riyan; Wahyu Hidayat, Puput; Guswita, Reni (Indonesian Journal of Innovation Studies, 2025)
General background: Parenting style plays a crucial role in shaping children’s development, influencing attitudes, behaviors, and academic outcomes. Specific background: In the Indonesian elementary context, particularly in communities with limited parental engagement due to socioeconomic factors, the quality of parenting may directly affect children’s learning achievements. Knowledge gap: Previous studies have mostly examined parenting and academic achievement broadly, without focusing on specific school contexts or applying rigorous statistical analysis at the elementary level. Aims: This study investigates the relationship between parenting styles and academic achievement among 19 fourth-grade students at State Elementary School 258/VI Rejo Sari. Results: Data collected through questionnaires and semester test scores were analyzed using Pearson correlation and simple regression. Findings revealed a significant positive relationship (r = 0.457, p = 0.049), with parenting style explaining 26.6% of achievement variance. Novelty: Unlike earlier descriptive studies, this research provides contextualized evidence within a specific school environment and employs quantitative methods to measure the statistical contribution of parenting. Implications: The results underscore the importance of parent–teacher collaboration, consistent home learning support, and structured motivation, offering practical recommendations for educators, parents, and policymakers to improve educational quality at the elementary level. Highlight: Parenting styles significantly shape student learning outcomes A quarter of achievement variance is explained by parenting Collaboration between parents and teachers is essential Keywords: Parenting Styles, Academic Achievement, Elementary School, Parent–Teacher Collaboration, Learning Support